Enrique García. The Hernandez Brothers: Love, Rockets, and Alternative Comics. Pittsburgh: U of Pittsburgh P, 2017. - Magda Garcia (Studies in 20th & 21st Century Literature, 2017)
Review of Enrique García. The Hernandez Brothers: Love, Rockets, and Alternative Comics. Pittsburgh: U of Pittsburgh P, 2017.
Keywords: U.S. Latino comics; postmodernism; sexuality